DEVELOPING A WEB-BASED DISCUSSION PLATFORM USING THE MERN STACK, TYPESCRIPT, AND FIREBASE STORAGE (Uzbekistan Open Conference, 2025)
This article examines the design and implementation of a full-featured web discussion platform. The platform is designed for publishing articles created using a built-in constructor and for conducting topic-based discussions in threads. MERN, which includes MongoDB, Express.js, React, and Node.js, was chosen as the primary technology stack. TypeScript was used to enhance client-side reliability and code typing. Static media files, such as images and videos, were managed using Firebase Storage. The paper describes all stages of development step by step: from designing the user interface in the Figma online service to implementing server-side logic in Node.js and client-side components in React. Key architectural decisions are covered in detail, including an authentication system based on JWT tokens, content creation and display modules, and the use of reusable components to optimize rendering. Particular attention is paid to the serverless approach to working with files, where their upload and storage occurs directly from the client to cloud storage, bypassing the server API, which reduces the overall load on the system.